La puntuación en los códices de la General Estoria de Alfonso X el Sabio - Pedro Sánchez-Prieto Borja (Atalaya)
The aim of this study is to examine the use of punctuation marks (pilcrow, dot and semi-colon) in the royal manuscripts of General estoria (First and Fourth parts). For this we have followed a method quantitative and qualitative on the first 100 folios of each manuscript. It is possible to establish the relative frequency of the use of each mark and to determine the contexts in which it appears, in order to figure out if punctuation has a preferably syntactic function or if it has other values. It is fundamental to examine the relationship between punctuation and syntax, and in particular whether or not the different marks used cut the syntactic progression. The results have been surprising. We have also compared segments of different sources and different syntactic configuration to determine if the internal typology of General estoria influences the use of punctuation marks.